Adenosine signaling in diabetes mellitus and associated cardiovascular and renal complications. (June 2017) - Peleli, Maria; Carlstrom, Mattias
Abstract: Diabetes mellitus is characterized by abnormal glucose and lipid metabolism, and subsequent hyperglycemia and dyslipidemia, which results from defects in pancreatic islet beta-cells insulin secretion and/or decreased insulin sensitivity in metabolically active organs ( i.e. liver, skeletal muscle and adipose tissue). Accumulating evidence highlights a critical role for the adenosine system in the regulation of insulin and glucose homeostasis and the pathophysiology of type 2 diabetes (T2D). Adenosine is a key diverse extracellular signaling molecule that regulates several aspects of tissue function by activating four G-protein-coupled receptors ( i.e. A1, A2A, A2B and A3 receptors). Moreover, adenosine receptor signaling plays a critical role in inflammation, immune system, and oxidative stress, factors that are also important in metabolic disorders. This review discusses the role of the adenosine receptor system in the development or progression of diabetes mellitus, with specific focus on T2D, and associated complications linked to the cardiovascular and renal systems.